Penanaman Karakter Disiplin dan Tanggung Jawab Berbasis Brand Sekolah (Studi Kasus di Kelas VI SDIT IQRA) - Marjohan Marjohan; Dase Erwin Juansah; Aan Hendrayana (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The aim of this research is to explore how school brands can be used as a tool to instill character in students through learning the Koran. This research uses a qualitative approach with a case study method, which involves in-depth interviews with teachers, school principals, students and parents, as well as direct observation of Al-Qur'an learning activities. Research findings show that a strong school brand, appropriate strategy and implementation, as well as an appropriate evaluation program to measure effectiveness play a significant role in establishing a learning environment that supports the cultivation of discipline and responsibility. The strategies implemented include collaboration with student parents, building commitment from teaching staff, setting clear and measurable targets, interactive learning activities, and implementing positive habituation programs in students' daily lives. Measuring and evaluating the effectiveness of cultivating the character of discipline and responsibility at SDIT IQRA Serang City is carried out through various activities involving all elements of the school, including teachers, students and parents. Measuring and evaluating the effectiveness of character cultivation includes tahfidz d exam activities, counseling for students and parents, coordination meetings as well as progress reports and program preparation. The conclusion of this research is that a school brand that is well designed and implemented can be an effective means of developing discipline and responsibility in students, which ultimately supports the achievement of learning targets as well as students' academic and non-academic achievements.